Influence of service temperature on shear creep behaviour of a rigid low-density closed-cell PIR foam. (20th November 2019) - Figueira, Diogo; Sena-Cruz, José; Pereira, Eduardo; Valente, Isabel; Barros, Joaquim; Castro, Fernando; Soares, Delfim
Highlights: A DMA test on the PIR foam has shown very high thermal stability between 0 and 40 °C. Shear creep behavior of PIR slightly varied in the temperature range of 20–30 °C. A stress amplitude of 30% was enough to cause nonlinear creep in the PIR foam. Shear creep analytical curves were successfully calibrated using Findley's power law. Abstract: An experimental campaign was carried out to assess shear creep behaviour of a rigid low-density closed-cell polyisocyanurate (PIR) foam. Two service temperature values were considered, 20 °C and 30 °C, and the applied stresses ranged between 20% and 60% of the corresponding shear strength. The results showed that a stress amplitude of 30% was enough to cause nonlinear creep response. Furthermore, creep deformations were slightly smaller in the tests at 30 °C, a fact that matched the viscoelastic response of the PIR foam obtained from DMA testing. Finally, creep prediction curves were calibrated through an analytical approach based on the Findley's power law.